NUTRITIONAL STATE OF CHILDREN AND ADOLESCENT OF THE MUNICIPAL DISTRICT OF PRESIDENT FIGUEIREDO - AMAZONAS (Fiep Bulletin - online, 2011)
The objective of the study was of analyzing the children's nutritional state and adolescents from seven to 18 years of age, of both sexes, visitors of the schools of the public net of the headquarters of the municipal district of President Figueiredo - AM. The sample was composed by 1261 boys and 1282 girls selected aleatoriamente, belonging to six schools of the headquarters of the municipal district. The variables weight, stature and date of birth and sex were analyzed. The data were submitted to the program of Evaluation and Nutritional State in Pediatrics (PED). the evaluation of the nutritional state was accomplished by the criteria, of peso/estatura and estatura/idade, being used as reference pattern the model of National Center it goes Health and Statistics (NCHS) and the classification of Waterlow. The results of the present study appeared for the values of the nutritional state, in that the children and adolescents, in all of the age groups, meet so much with nutritional deficit (prevalence for malnutrition), as well as some problem related to the weight excess. In prominence for the ages of 11, 14 and 17 years, with prevalence for past malnutrition. They were observed, for the variables of corporal weight and stature, smaller values to the study of NCHS and the Program of Family Budget (POF).
Keywords: Nutritional state; children's evaluation and adolescents